Homology-mediated inter-chromosomal interactions in hexaploid wheat lead to specific subgenome territories following polyploidization and introgression - Jizeng Jia; Yilin Xie; Jingfei Cheng; Chuizheng Kong; Meiyue Wang; Lifeng Gao; Fei Zhao; Jingyu Guo; Kai Wang; Guangwei Li; Dangqun Cui; Tiezhu Hu; et al. (Genome Biology, 2021)
Abstract Background Polyploidization and introgression are major events driving plant genome evolution and influencing crop breeding. However, the mechanisms underlying the higher-order chromatin organization of subgenomes and alien chromosomes are largely unknown. Results We probe the three-dimensional chromatin architecture of Aikang 58 (AK58), a widely cultivated allohexaploid wheat variety in China carrying the 1RS/1BL translocation chromosome. The regions involved in inter-chromosomal interactions, both within and between subgenomes, have highly similar sequences. Subgenome-specific territories tend to be connected by subgenome-dominant homologous transposable elements (TEs). The alien 1RS chromosomal arm, which was introgressed from rye and differs from its wheat counterpart, has relatively few inter-chromosome interactions with wheat chromosomes. An analysis of local chromatin structures reveals topologically associating domain (TAD)-like regions covering 52% of the AK58 genome, the boundaries of which are enriched with active genes, zinc-finger factor-binding motifs, CHH methylation, and 24-nt small RNAs. The chromatin loops are mostly localized around TAD boundaries, and the number of gene loops is positively associated with gene activity. Conclusions The present study reveals the impact of the genetic sequence context on the higher-order chromatin structure and subgenome stability in hexaploid wheat. Specifically, we characterized the sequence homology-mediated inter-chromosome interactions and the non-canonical role of subgenome-biased TEs. Our findings may have profound implications for future investigations of the interplay between genetic sequences and higher-order structures and their consequences on polyploid genome evolution and introgression-based breeding of crop plants.